Advancing Odisha’s Millet Mission: A Science-Policy Workshop Highlighting Transformative Pathways - Kumar, Shalander; Das, Abhishek; Afari-Sefa, Victor; Datta, Aviraj (International Crops Research Institute for the Semi-Arid Tropics, 2025)
ICRISAT, in partnership with the Odisha University of Agriculture and Technology (OUAT), organized a Science-Policy Workshop on Advancing the Mainstreaming of Millets into Agri-food Systems in Odisha: Learnings, Insights, and Way Forward. The workshop was held in Bhubaneswar on 26 December 2024 under the aegis of the CGIAR National Policies and Strategies Initiative. Focused on strengthening efforts to mainstream millets, the meeting attracted participation from researchers, policymakers, and representatives from Odisha's millet value chain. Participants explored various aspects of the millet value chain, including enhancing production and farmer capacity, market development and value addition, consumer awareness, and demand creation.